Preying for Monopoly? The Case of Southern Bell Telephone Company, 1894-1912 - Weiman, David F.; Levin, Richard C. (Journal of Political Economy, 1994)
Focusing on the Southern Bell Telephone Company, we propose a modified version of the predation hypothesis to explain Bell's "natural" monopoly over local telephone service. Southern Bell effectively eliminated competition through a strategy of pricing below cost in response to entry, which deprived competitors of the cash flow required for expansion even if it failed to induce exit; investing in toll lines ahead of demand, isolating independent companies in smaller towns and rural areas, and forcing them to consolidate on favorable terms; and influencing local regulatory policy in large cities to weaken rivals and ultimately to institutionalize the Bell monopoly.